Pelatihan Manajemen Kandang Itik Pedaging Sebagai Upaya Peningkatan Perekonomian Masyarakat - Rizal, Fitra; Sholihah, Imroatus; Nur Farichan, Mu’aifi; Zainul Ihrom, Mohammad (Institut Agama Islam Negeri Ponorogo, 2023)
Abstract: Management, as a process of designing and maintaining a collaborative environment, is applied to address the popularity of livestock farming in Caluk Village, particularly duck farming. The goal is to establish an advanced and efficient farm, but the challenge lies in the community's limited knowledge and experience in barn design and waste management. Employing the Asset-Based Community Development (ABCD) approach, the initiative optimizes existing assets and potentials. The outcome is the creation of an ideal duck farm that effectively manages waste. Training provided proves instrumental in enhancing the community's duck farming practices, leading to improved farmer well-being and a positive economic impact on the surrounding community.